Etiological agents causing paediatric sepsis and their antimicrobial susceptibility pattern at a tertiary care hospital - Husain A; Agarwal S; Jafar H; Awasthi S; Prakash V (Journal of Medical and Scientific Research)
Background: Paediatric septicemia causes significant global morbidity and mortality, particularly in resource-poor regions. The knowledge of microbiological profile of sepsis in children is utmost important to guide the treatment. This study aims to investigate the prevalent pathogens and their antimicrobial susceptibility pattern in cases of pediatric sepsis in a tertiary care hospital.